(untitled) (Bioscience Journal, 2014)
The composition and diversity of aquatic insect fauna can be influenced by several factors such as substrate type, availability of allochthonous material, biotic interactions, among others. This occurs because these organisms have different adaptations to environmental characteristics of aquatic systems. The aim of this work was to evaluate the distribution and seasonal variation of immature insects of the Ephemeroptera, Plecoptera and Trichoptera orders in different environments at a Cerrado area in Uberlândia - MG. Sampling was performed in August 2007 (dry season) and February 2008 (rainy season), in three types of environment (stream in gallery forest, stream in vereda and in a pond) at "Reserva do Clube de Caça e Pesca Itororó". The insects were sampled using artificial substrates. We collected a total of 205 insects, 96 in the dry season and 109 in the rainy season. Differences in the abundance of insects among environments were recorded only for Ephemeroptera. Despite distinct characteristics of each environment the abundance of organisms and the richness of genera were similar among sampling sites and between seasons. However, there was a variation in the composition of organisms in each environment.